Estimation of the willingness-to-pay for preserving football arena in Gdansk - Krystian Zawadzki (e-Finanse: Financial Internet Quarterly, 2015)
The European Football Championship (Euro 2012) organized in Poland became the pretext for a number of infrastructural changes. A high level of expenditure makes the Polish event the most expensive among events of this magnitude. The fact that these changes were 100% financed by public funds raises the question of whether these funds were used in a substantiated way. Therefore, the aim of this study is to estimate the willingness-to-pay (WTP) among the community of the Pomeranian region, in connection with the construction of the stadium in Gdansk. A survey conducted among 299 respondents was the source of information. The results of the study show that the average value of WTP for the whole sample was 6.71 EUR2012, while the aggregate value for the whole region was 15.4 million EUR2012. The regression analysis showed that the level of WTP is determined in particular by income levels. The results thus confirm the existence of intangible benefits associated with the constructed facilities. However, it should be noted that the importance of these benefits is insignificant and does not compensate for the massive expenditure from public sources.
Keywords: H41; I31; H54; 330; mega sports events; Euro 2012; CVM; Public funds; WTP